2015
DOI: 10.3402/gha.v8.26318
|View full text |Cite
|
Sign up to set email alerts
|

Referral outcomes of individuals identified at high risk of cardiovascular disease by community health workers in Bangladesh, Guatemala, Mexico, and South Africa

Abstract: BackgroundWe have found that community health workers (CHWs) with appropriate training are able to accurately identify people at high cardiovascular disease (CVD) risk in the community who would benefit from the introduction of preventative management, in Bangladesh, Guatemala, Mexico, and South Africa. This paper examines the attendance pattern for those individuals who were so identified and referred to a health care facility for further assessment and management.DesignPatient records from the health centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 15 publications
4
58
0
Order By: Relevance
“…The Kenyan STEPS survey reported that only 12% of Kenyans have ever had their blood glucose tested by a healthcare professional 2. A cross-sectional study conducted by public health officials in Kenya showed that only 27% of participants had a good understanding of diabetes 25. Given the current knowledge about the lack of diabetic testing in Kenya, it is probable that our 3.2% prevalence rate for diabetes is an under representation of the actual number of those living with diabetes in the region.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Kenyan STEPS survey reported that only 12% of Kenyans have ever had their blood glucose tested by a healthcare professional 2. A cross-sectional study conducted by public health officials in Kenya showed that only 27% of participants had a good understanding of diabetes 25. Given the current knowledge about the lack of diabetic testing in Kenya, it is probable that our 3.2% prevalence rate for diabetes is an under representation of the actual number of those living with diabetes in the region.…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted by Levitt et al 25 used trained CHWs to implement a non-laboratory-based CVD risk model to identify high-risk patients in Bangladesh, Guatamala, Mexico and South Africa. They found that 77.4% of patients were at low risk, 17.4% were at low to moderate risk, 3.7% were at moderate risk, 1.1% were at moderate to high risk and 0.2% were at high risk.…”
Section: Discussionmentioning
confidence: 99%
“…The rates at which referred people (those whose cardiovascular disease risk score was over 20 percent) completed a visit to a primary health center were as low as 33 percent in the three countries in our study. 17 Formal studies are needed to evaluate how mobile health tools can also be used for improving referral rates and initiation of appropriate treatment at primary health centers.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work established that of those referred to treatment, approximately 37 percent overall and 69 percent of those at highest risk actually visited a local clinic within the recommended two weeks of screening. 17 However, each country has different rates of initiation for treatment with essential blood pressure medications or statins. We therefore used current treatment rate information for hypertension from published surveys for each country studied 25–27 (Appendix Exhibit A7).…”
Section: Study Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation